Body Dissatisfaction in Women Across the Lifespan: Results of the UNC‐SELF and Gender and Body Image (GABI) Studies. (5th September 2012) - Runfola, Cristin D.; Von Holle, Ann; Trace, Sara E.; Brownley, Kimberly A.; Hofmeier, Sara M.; Gagne, Danielle A.; Bulik, Cynthia M.
Abstract To explore age differences in current and preferred silhouette and body dissatisfaction (current − preferred silhouette discrepancy) in women aged 25–89 years using figural stimuli [range: 1 (very small) to 9 (very large)]. Data were abstracted from two online convenience samples (N = 5868). t‐tests with permutation‐adjusted p‐values examined linear associations between mean silhouette scores (current, preferred, discrepancy score) and age with/without stratification by body mass index (BMI). Modal current silhouette was 5; modal preferred silhouette was 4; mean discrepancy score was 1.8. There was no significant association between current silhouette and age, but a positive linear association between preferred silhouette and age remained after stratification by BMI. A significant inverse linear association of silhouette discrepancy score and age was found only prior to stratification by BMI. Body dissatisfaction exists in women across the adult life span and is influenced by BMI. Copyright © 2012 John Wiley & Sons, Ltd and Eating Disorders Association.